Low voltage low power output programmable OCL-LDO with embedded voltage reference - Nardi, Utomo (2021)
The low voltage low power output-capacitorless (OCL) low dropout regulator (LDO) with embedded voltage reference (EVR) with adjustable and programmable output voltage is proposed in this paper. With the proposed design, the embedded voltage reference (EVR) LDO can provide desired output voltages of 435mV, 500mV, 550mV, and 600mV in single LDO design. The dropout voltage is 60mV for low power consumption. The proposed circuit is implemented and simulated in 55nm CMOS technology. The circuit consumes 30μA of quiescent current and 0.0234mm 2 chip area. Simulation results show that the line regulation is below 12.5mV/V, load regulation is below 2.6mV/mA and temperature coefficient (TC) is below 59ppm/ o C under all different output voltage modes of the LDO. Stability of the proposed design is also verified in simulation. The design also has fast transient recovery time of less than 1.67μs under 100ns rise/fall time load current transient.